Strategic Agility and Organizational Performance: The Mediating Role of Digital Transformation in Indonesian SMEs - Hidayat, Agus Rohmat; Hardiyanto, Feri; Alifah, Nur; Rodiansjah, Agis Ahmad (GEMA EKONOMI, 2026)
Backround: SMEs in Indonesia face rapid environmental changes driven by digital disruption and global competition. Strategic agility is essential for adapting to these dynamics, yet how it improves organizational performance remains unclear. Digital transformation is expected to act as a key mechanism linking agility to performance within the frameworks of dynamic capability theory and the resource-based view.Objective: This study examines the mediating role of digital transformation in the relationship between strategic agility and organizational performance among Indonesian SMEs.Method: A quantitative approach was applied using SEM-PLS on data from 380 SME owners and managers across six provinces. Measurement model evaluation included reliability (Cronbach’s alpha) and validity (AVE), while structural analysis assessed path relationships and mediation effects.Result: The measurement model demonstrated strong reliability and convergent validity across all constructs. Strategic agility exerted a significant positive influence on both digital transformation and organizational performance. Furthermore, digital transformation was found to partially mediate the relationship between strategic agility and organizational performance, confirming the proposed sequential mechanism.Conclusion: Digital transformation strengthens the impact of strategic agility on organizational performance. The findings highlight the importance of integrating agility and digital capabilities to enhance SME competitiveness and sustain performance in the digital era.